EFEKTIVITAS PEMBERIAN HEALTH EDUCATION â€œSADARIâ€ MENGGUNAKAN LEAFLET DAN PHANTOM TERHADAP TINGKAT PENGETAHUAN SISWI KELAS X DALAM UPAYA PENCEGAHAN CA MAMMAE: Array (Midwinerslion : Jurnal Kesehatan STIKes Buleleng, 2018)
Introduction: Prevention of ca mammae can be done by early detection of breast self-examination where mortality can be reduced by 15-30%. However, in reality only 15-30% are doing BSE. So it takes the BSE movement that is accompanied by the concept of breast awareness of health education. This research aimed to identify the effectiveness of health education of â€œBSEâ€ using leaflets and phantom to the level of knowledge in prevention efforts ca mammae. Methods: This research uses True Experimental Pretest-Posttest With Control Group design with quantitative research approach. Samples totaling 39 peoplewere obtained through Total Sampling technique. Data colletion using questionnaires and analyzed using Paired Dependent T Test and group comparasion using Mann Whitney Test. Result: The result of statistical test that the value of p value of 0,032 < 0,0. Conclution: hence there is different of effectiveness giving health education â€œBSEâ€ using leaflet and phantom to knowledge level. Mann Whitney Test result show an effective tool is phantom.